Glufosinate-Ammonium Induced Aberrant Histone Modifications in Mouse Sperm Are Concordant With Transcriptome in Preimplantation Embryos - Ma, Xuan; Fan, Yun; Xiao, Wenwen; Ding, Xingwang; Hu, Weiyue; Xia, Yankai (Frontiers in Physiology, 2022)
Glufosinate-ammonium (GLA) is a widely used herbicide with emerging concern over its male reproductive toxicity. Abnormalities in sperm histone modification induced by GLA exposure observed in our previous study aroused our interest in whether such alterations could further affect embryonic gene expression. Here we administered adult male mice with 0.2 mg/kg⋅day of GLA for 5 weeks to collect their sperm or 4-cell embryos after copulation. Cleavage Under Targets & Tagmentation (CUT&Tag) sequencing showed alterations of sperm H3 lysine 4 trimethylation (H3K4me3) and histone H3 lysine 27 acetylation (H3K27ac), which are active histone modification marks involved in embryo development, while RNA sequencing identified differentially expressed genes in 4-cell embryos. Differentially H3K4me3 and H3K27ac occupied regions were mainly distributed at the gene promoters and putative enhancers, and were enriched in pathways related to immune system and nervous system. Integrative analysis of these sequencing data showed that genes such as Mgl2 with increased H3K4me3 and H3K27ac in sperm were up-regulated in embryos, and vice versa for genes such as Dcn. Additionally, differentially occupied H3K4me3 and H3K27ac in sperm were linked to gene expression changes in both paternal and maternal alleles of 4-cell embryos. In conclusion, GLA-induced changes in sperm H3K4me3 and H3K27ac are concordant with gene expression in preimplantation embryos, which might further affect embryo development and offspring health.